CONGRESS OF THE AMERICAN COLLEGE OF CARDIOLOGY 2010: CRISIS OF CLINICAL GUIDELINES - S. Yu. Martsevich; Yu. V. Lukina (Рациональная фармакотерапия в кардиологии)
Congress of the American College of Cardiology 2010: crisis of clinical guidelines.